Jantzen and Sedlmayr: Diaphaneia—an impossible presence? - Vaneyan, Stepan (Interstices: Journal of Architecture and Related Arts, 2019)
The immediacy of visual experience has always appeared as an indicator of verifiability of a presence. However, architecture as a bodily presence seems to be a reality that does not need verification. Yet there remains the issue of sacral architecture, which strives for the transcendent. What can be a medium in the experience of theophany?Sacral experience of Gothic architecture is very suitable for such observations. However, as I hope to demonstrate, only one theory seems to have actually approached the understanding of interconnections between the Holy Presence and the experience of it on an architectonic level. Precisely, it is Hans Jantzen’s (1881-1967) programmatic theory of “a diaphanic structure”.Term “diaphaneia” was first introduced by Jantzen in his article “Über den gotischen Kirchenraum” (1927). By that time the word had been used in near-esoteric circles (from Jacob Boehme to Pierre Teilhard de Chardin and James Joyce). Jantzen’s seminal article is dedicated to the space of the Gothic cathedral, which he sees as ritual-liturgical. It is this multilayered space, he argues, that has a “diaphanic structure”. In his late texts (from the 1950 and 1960s) diaphaneia is explored as a universal way of keeping in view the horizon of the invisible presence. Sedlmayr's perception of Jantzen's ideas shows that optical diaphaneia should be complemented with somatic diaphaneia  (through “baldachin”, in Sedlmayr's structuralist terms).The ultimate question is if diaphaneia is merely a means of “spiritualisation” of both the cathedral per se and architectural theory. Although architecture keeps silent, an architectural theorist speaks: using Derrida’s words, diaphaneia becomes diaphonie.